The in vitro and in vivo effects of nicotine on bone, bone cells and fracture repair. (March 2013) - Kallala, Rami; Barrow, Jonathan; Graham, Simon Matthew; Kanakaris, Nikolaos; Giannoudis, Peter V
<x xml:space="preserve">Abstract</x> Introduction: Cigarette smoke has negative effects on bone metabolism and fracture repair. However, no study has reviewed effects of nicotine on bone and fracture repair independent of other constituents of cigarette smoke. The authors review the existing evidence of the effect of nicotine on 'bone' and 'bone cells' and fracture repair, drawing conclusions relevant to clinical practice and future research. Areas covered: A literature review was conducted using PRISMA guidelines and PubMed, Cochrane, MEDLINE/OVID, EMBASE, NHS Evidence and Google scholar databases. Articles were included if they specifically investigated the effects of nicotine on 'bone' or fracture repair in animal or human models or in vitro effects on 'bone cells'. A total of 64 papers were included in this review, of which 15 were human in vitro studies and 49 animal studies wherein 9 were in vitro and 40 in vivo.In vivo studies of the effects of nicotine in animals demonstrated widespread effects on bone including osteoneogenesis, osseointegration, steady-state skeletal bone and genes and cytokines relevant to bone cell physiology and bone homeostasis. In these studies, nicotine's effects are predominately negative, inhibiting bone cell metabolism and fracture repair, whereas most in vitro studies reported biphasic responses in all bone cells except osteoclastic cells. Expert opinion: The review suggests that nicotine has effects on osteoneogenesis, osseointegration and steady-state skeletal bone in animal in vivo models, as well as effects on all 'bone cells', via several mechanisms in both animal and human cell in vitro studies. The effect of nicotine is dose-dependent, with higher concentrations having predominantly negative effects, whereas at low concentrations a stimulatory effect is seen. Stimulatory effects on certain cells may indicate a possible, limited therapeutic role; advice regarding smoking cessation perioperatively should remain due to the other harmful components of cigarette smoke, but there may be scope for allowing the use of nicotine patches instead of complete abstention. Further research into clinical outcomes is required before the exact response of bone and fracture repair in humans to nicotine is known.